Enhancing management of technology and innovation for sustainable competitiveness of SMEs - Phi, Hoang Dinh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2011)
Abstract. Being impacted by the financial and economic crises and the threats of economic downturn spiral, social unrest and environmental pollutions…, businesses and people are talking a lot about sustainable development as a target, a desire and an aspiration of human beings in the 21 st century. In many countries, small and medium enterprises (SMEs) hold a large number and play a very important role in the sustainable development. How to build and develop sustainable competitiveness for SMEs still remains an unanswered question for many governments. This paper introduces a new approach and a basic tool that SMEs can apply to build sustainable competitiveness in the context of global cooperation, competition, and integration.   Keywords: Technology, innovation, sustainable competitiveness.